Research advancements of antibody drug conjugates in non-small cell lung cancer with HER2 alterations - Jiang Liu; Jianhua Liu; Jianhe Yu; Qun Ren; Yin Cai; Dadong Chen; Chuanjun Song (Journal of Translational Medicine)
Abstract The human epidermal growth factor receptor 2 (HER2) alterations are significant genetic alterations in non-small cell lung cancer (NSCLC), encompassing mutations, amplifications, and protein overexpression. Despite the substantial progress of anti-HER2 targeted therapies in breast and gastric cancers, numerous challenges persist in the treatment of NSCLC with HER2 alterations. Presently, the options for NSCLC with HER2 alterations remain limited, with inferior efficacy observed using small molecule anti-tumor targeted agents and conventional chemotherapy. Antibody drug conjugates (ADCs), an organic combination of monoclonal antibodies and cytotoxic drugs targeting specific tumor cells, have revolutionized the treatment landscape of NSCLC with HER2 alterations. Extensive exploration of ADCs has been conducted across NSCLC patients with HER2 alterations, achieving notable efficacy in some populations. This review aims to delve into the biological characteristics and current treatment landscape of NSCLC with HER2 alterations, emphasizing the transformative research advancements surrounding ADCs. By highlighting these developments, we aspire to provide essential insights to enhance clinical practice and improve management strategies for NSCLC patients with HER2 alterations.